2023
DOI: 10.1038/s44172-023-00053-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrically stimulated optical spectroscopy of interface defects in wide-bandgap field-effect transistors

Abstract: Wide-bandgap semiconductors such as silicon carbide, gallium nitride, and diamond are inherently suitable for high power electronics for example in renewable energy applications and electric vehicles. Despite the high interest, the theoretical limit regarding device performance has not yet been reached for these materials. This is often due to charge trapping in defects at the semiconductor-insulator interface. Here we report a one-to-one correlation between electrically stimulated photon emission and the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…This spectrum can be understood as a fingerprint of the radiative electronic interface transitions with distinct peak energies. The target of future research will be to further refine this optical methodology and to correlate the characteristic peaks in the spectrum to defect types suggested by theoretical calculations [9,10]. Also, correlating defect-specific emission peaks to findings of alternative methods that provide structural defect information such as electrically detected magnetic resonance [19,20] could lead to a deeper understanding of the nature of the involved defects.…”
Section: Spectroscopy Of Interface Radiation To Reveal the Nature Of ...mentioning
confidence: 99%
“…This spectrum can be understood as a fingerprint of the radiative electronic interface transitions with distinct peak energies. The target of future research will be to further refine this optical methodology and to correlate the characteristic peaks in the spectrum to defect types suggested by theoretical calculations [9,10]. Also, correlating defect-specific emission peaks to findings of alternative methods that provide structural defect information such as electrically detected magnetic resonance [19,20] could lead to a deeper understanding of the nature of the involved defects.…”
Section: Spectroscopy Of Interface Radiation To Reveal the Nature Of ...mentioning
confidence: 99%
“…Aside from room temperature measurements, which have been already investigated in [4,5], we also conducted experiments at cryogenic temperatures to investigate the impact of reduced thermal energy onto the radiative process and to ease defect identification. Once a charge carrier is trapped in a defect state, the branching ratio of radiative versus non-radiative detrapping increases.…”
Section: Experimental Approachmentioning
confidence: 99%
“…When the atomic defect configurations of interface traps are known, the development of defect density reducing techniques is facilitated. Here, we use energy-resolved electroluminescence measurements [3,4,5,6] at cryogenic temperatures in combination with ab initio calculations to characterize the SiC/SiO 2 -interface. During the measurement the gate is switched between accumulation and inversion which results in radiative carrier recombinations via mid gap defects.…”
Section: Introductionmentioning
confidence: 99%
“…Measuring point defects at the interface after fabrication often involve destroying the delicate device architecture or fabricating dedicated test structures to investigate the interface. An article by Feil et al 3 published a clever alternative in Communications Engineering , etching back the device substrate to spectroscopically probe the field-effect stimulated radiative defect transitions from the underside of wide-bandgap semiconductor metal-oxide-semiconductor field-effect transistors. A contrast between their approaches and those of previous works can be found in Fig.…”
Section: Electrically Stimulated Optical Spectroscopy Of Interface De...mentioning
confidence: 99%
“…1 Illustration of optical top-side detection (approach reported in previous studies) and reverse-side detection (approach reported here). Reused from 3 . …”
Section: Electrically Stimulated Optical Spectroscopy Of Interface De...mentioning
confidence: 99%